Pan-cancer analysis of CLDN1 and its functional study in gastric cancer - Zhu Weijing; Zhang Jiaxing; Wei Yucai; Yang Shengrui; Wang Wenxuan; Li Yumin (生物医学转化)
Objective This study employs bioinformatics methods to analyze the expression of Claudin 1 (CLDN1) across various types of cancer and its functional role in gastric cancer. Methods The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases were used to evaluate the expression patterns of CLDN1 in various cancer types and their association with clinical pathology, patient prognosis, and immune characteristics. Western blotting, Polymerase Chain Reaction(PCR), and cell function assays were used to examine the expression and function of CLDN1 in gastric cancer cells. Results CLDN1 was significantly upregulated in 13 types of tumors and downregulated in 7, with a strong correlation to tumor stage and grade. It demonstrated good diagnostic potential and was associated with poor prognosis in 8 cancer types. Additionally, CLDN1 showed the highest mutation rate in lung squamous cell carcinoma. Immune analysis revealed significant correlations between CLDN1 expression and immune infiltration, immune checkpoint gene expression, tumor mutation burden, and microsatellite instability across most cancer types. CLDN1 was highly expressed in MKN45 cells, and its knockdown significantly reduced cell proliferation and migration. Conclusion CLDN1 exhibits significant expression heterogeneity across various cancers, with strong associations with diagnosis, prognosis, clinical characteristics, and immune profiling. It represents a potential diagnostic marker and therapeutic target in cancer treatment.